SOSIALISASI PROSEDUR PELAKSANAAN KONSELOR SEBAYA PADA MUSYAWARAH GURU BIMBINGAN DAN KONSELING DI KOTA PALU - Ridwan Syahran; Mardi Lestari; Azam Arifyadi; Dian Fitriani; Nur Eka Wahyuningsih Riyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tunas Pembangunan Surakarta (UTP), 2025)
The problems of this service are; 1) The process of guidance services to students in junior high schools in Palu City is not yet optimal; 2) Junior high school guidance and counseling teachers in Palu City who have not fully optimized the role of peer counselors in providing guidance services to students. The purpose of this service is to improve the understanding, skills, and abilities of junior high school guidance and counseling teachers in Palu City in carrying out services at school. The subjects of this service are junior high school counseling teachers who are members of the Consultation of Guidance and Counseling Teachers (MGBK) in PALU City. The stages of implementing this service through socialization and mentoring. The achievement of this service is that teachers can apply, optimize and carry out the implementation of peer counselors for students in the process of guidance and counseling services at school.